The association between serum leptin, adiponectin and resistin levels with chronic kidney disease with and without hemodialysis patients - Maha Elttayef Jasim; Firas Faris Rija; Sura Zahim Hussein (Endocrine and Metabolic Science)
Chronic kidney disease (CKD) is major and urgent public health problem caused by a progressive reduce in renal function during some months or years which cause functional or structural abnormalities of the kidney. In renal failure, many adipokines are important in endothelial dysfunction, like inflammation and oxidative stress. This study aims to evaluate the changes of some adipokines in chronic kidney disease (CKD) with and without hemodialysis (HD) Patients. Blood samples were collected from dialysis Unit in Tikrit Teaching Hospital in Tikrit city which started from January- July 2024 who aged (18 - 68) years old. The study subjects were 90 individuals who consist of 30 healthy individuals, 30 CKD patients with hemodialysis treatment and 30 CKD patients without hemodialysis treatment. The present study showed that leptin, adiponectin and resistin were increased in CKD patients with HD and (adiponectin and resistin) were decreased in CKD patients without HD while leptin was increased in CKD patients without HD when compared with control group. Adipokines changes in hemodialysis patients rather than pre dialysis CKD patients.